20-20-20 rule: an effective method for coping with computer vision syndrome - Muhammad Muneeb; Bacha, Zaryab (Journal of the Pakistan Medical Association, 2025)
Dear editor, As the use of electronic devices continues to escalate, computer vision syndrome is becoming increasingly prevalentarrange, especially among medical students. One of the most effective strategies to manage computer vision syndrome (CVS) is the 20-20-20 rule, in which the person shifts his focus from the electronic device to an object placed at 20 feet for 20 seconds every 20 minutes. CVS is characterised by headache, blurred vision, neck pain, eyestrain, itchy eyes, diplopia, and trouble focusing the eyes.1 Computer vision syndrome is a growing concern among medical students as more and more students are transition to using electronic devicesfor study instead of using traditional books. The academic demands, extensive courses, and sleep deprivation make medical students one of the most important communities vulnerable to CVS. However, according to a recent study, only 34.1% of medical students are aware of CVS and the strategies to manage it; preventive strategies such as the 20-20-20 rule.2 CVS is caused by a decreased blink reflex, which occurs when individuals work on a computer for long periods. The normal blinking frequency is substantially reduced from 16-20 times per minute to 6-8 times per minute in people who use computers.3 The 20-20-20 rule is an effective method for reducing the symptoms of CVS. This method has been found to reduce the severity and incidence of CVS among medical students.3 According to a study, taking a short break when using electronic equipment every 20 minutes reduces the prevalence of CVS by 7%.4 These findings underscore the need for strategies that reduce continuous screen use through frequent breaks, rather than solely limiting screen time.5 In contrast to more complex approaches, the 20-20-20 rule stands out for its ease of implementation, minimal effort, and is just a matter of developing a habit. This method ultimately helps to increase student's productivity, alleviate eyestrain, and reduce neck pain and headache. In order to implement the 20-20-20 rule effectively, certain measures should be taken such as setting up a reminder on the laptop to take regular breaks, choosing a specific distant object to focus on, and placing the laptop at a proper viewing distance. In conclusion, there is a need to create awareness about this useful technique among medical students to safeguarding ocular healthand increase productivity in the long run. Therefore, awareness sessions and workshops should be organise in medical colleges to educate students about the 20-20-20 rule.